Perspectives of Nurses on Organizational Culture - Zahra Ahmadian; Mansoureh Ashghali Farahani; Farideh Bastani; Hamid Haghani (Tehran University of Medical Sciences, 2012)
Background & Objective: Hospitals and healthcare centers, like any other organizations, have some common norms and beliefs called as organizational culture. Organizational culture plays a key role in organization&aposs and staffs&apos performances. Nurses&apos perspectives on the organizational culture affect the way they play their role in. This study aimed to investigate the role of organizational culture from perspectives of nurses working in selected hospitals at Tehran University of Medical Sciences. Methods & Materials: In this cross-sectional study, 230 nurses working in different wards of selected hospitals of Tehran University of Medical Sciences were recruited to the study. Data were collected using a demographic characteristics checklist as well as the nurse and organizational culture questionnaire extracted from the Robbins criteria. Data were analyzed using descriptive statistical indexes, independent t-test, Pearson correlation coefficient and regression in the SPSS v.17. Results: Results showed that the existing organizational culture in the selected hospitals was in a moderately good level from nurses&apos perspectives. From the scores obtained for various dimensions of the organizational culture, the highest and lowest scores were for control (44.2%) and conflict tolerance (31.8%), respectively. Conclusion: The level of the organizational culture from the nurses&apos perspectives might lead them to decrease the quality of their performance. Optimizing the organizational culture can improve nurses&apos performance and motivate them to increase their quality of work.